IDENTIFIKASI SEBARAN MINERALISASI LOGAM SULFIDA MENGGUNAKAN METODE POLARISASI TERINDUKSI DAN MAGNETIK DI KABUPATEN DAIRI, SUMATERA UTARA: IDENTIFICATION OF METAL SULFIDE MINERALIZATION USING INDUCED POLARIZATION AND MAGNETIC METHODS IN DAIRI REGENCY, NORTH SUMATRA - Farizan Qurunulbahri; Dzil Mulki Heditama; Hartaja M. Hatta Wicaksono (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2025)
Sulfide ore exploration is a critical focus in mining as it is a primary source of various metals needed in industry. In Indonesia, the potential for sulfide mineral resources is significant, particularly due to the complex geological conditions that create an ideal environment for forming sulfide mineral deposits. Geophysical methods, such as geoelectrics (resistivity and Induced Polarization) and magnetic methods, have effectively evaluated the potential for sulfide mineralization beneath the surface. This study was conducted in Dairi Regency, North Sumatra, to explore the potential for sulfide mineralization, particularly related to gold and base metals commodities. The results show the characteristic anomaly responses of rocks containing ore deposits with varying resistivity, chargeability, and susceptibility values. The characteristics of rock anomaly responses containing ore deposits at the study site show resistivity values ranging from low to high (1 - 86910 Ωm), chargeability values ranging from moderate to high (110 - 611 msec), and susceptibility values ranging from moderate to high (-0.4 - 1 × 10-5 SI). There is a correlation between these values, where zones with medium to high chargeability are associated with low to medium resistivity and medium susceptibility, indicating sulfide mineralization zones in argillic alteration. Meanwhile, zones with medium to high chargeability are associated with medium to high resistivity and medium to high susceptibility, indicating sulfide mineralization zones in phyllic alteration. The distribution of mineral deposits tends to orient west-east, consistent with the trend direction of quartz veins.